METHOD FOR ALARMING EQUIPMENT AND METHOD FOR MANAGING MAINTENANCE OF EQUIPMENT - OKUMURA HIRONOBU (2004)
PROBLEM TO BE SOLVED: To simplify the constitution of equipment and a management device by clarifying which accounts for an alarm of the equipment, a manufacturer (or maintenance supervisor) or a user (or contractor), quickly dealing abnormality of the equipment and reducing the number of alarms of the equipment. SOLUTION: In an equipment alarming method for alarming the abnormality of the equipment to a maintenance management device arranged on a remote place, which is generated, a 1st alarm for informing of the abnormality of an equipment body 2 or a 2nd alarm for informing of abnormality of an object other than the equipment, is discriminated in accordance with the contents of abnormality of the equipment and at least one of the 1st and 2nd alarms is transmitted to the maintenance management device 3 on the basis of the discriminated result. COPYRIGHT: (C)2004,JPO&NCIPI